Analysis of the Determinants of the Agricultural and Trade Sectors on Economic Growth Rate - Harahap, Bagus Hermansyah; Yusrizal; Tambunan, Khairina (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2026)
Purpose: This research examines the effect of the agricultural and trade sectors on regional economic growth in Deli Serdang Regency from 2015 to 2024, using Gross Regional Domestic Product (GRDP) data.Design/Methodology/Approach: A quantitative approach was applied using multiple linear regression models to analyze the relationship between the agricultural and trade sectors and regional economic growth. Data from the Deli Serdang Central Statistics Agency (BPS) were utilized, and the analysis was conducted with a focus on determining the contributions of these sectors to GRDP.Findings: The results indicate that both the agricultural and trade sectors have a significant simultaneous effect on GRDP, with an R² value of 0.892, meaning 89.2% of the variation in GRDP is explained by the contributions of both sectors. The agricultural sector showed a statistically significant positive contribution, while the trade sector, though positive, did not have a statistically significant impact.Practical Implications: The findings highlight the importance of sectoral synergy in driving inclusive and sustainable regional development. Effective strategies to integrate the agricultural and trade sectors can promote equitable economic growth.Originality/Value: This study contributes to the literature on regional economic growth by providing empirical evidence of the simultaneous contributions of the agricultural and trade sectors, underpinned by Islamic economic principles, particularly the protection of wealth, distributive justice, and the pursuit of collective welfare.